Duodenal juice total protein and pancreatic enzyme synthesis, turnover, and secretion in patients after acute pancreatitis. Issue 9 (September 1993) - Ogden, J M; O'Keefe, S J; Louw, J A; Adams, G; Marks, I N
Abstract : It is controversial whether acute pancreatitis has longterm effects on pancreatic function. Pancreatic enzyme synthesis, turnover, and secretion were measured in 10 patients in clinical remission who had had one or more (one to six) attacks of acute alcoholic pancreatitis. The studies were done between two and 29 months after the most recent attack. A control group included five patients with no evidence of pancreatic disease. A four hour primed/continuous intravenous infusion of [14C]L-leucine tracer was given with secretin (2 U/kg/h) and cholecystokinin (0.5 U/kg/h) and secreted duodenal juice aspirated. Amylase and trypsin were extracted from duodenal juice by affinity chromatography, permitting measurement of the rate of isotope incorporation into total protein, amylase, and trypsin. The results showed non-parallel changes in enzyme synthesis and turnover with decreases in total enzyme protein and amylase synthesis and turnover but preservation of trypsin synthesis and turnover. The low turnover rates may be ascribed to continuing pancreatic cell malfunction after recovery from acute alcoholic pancreatitis and suggest that the decreased amylase secretion rates are partly a consequence of impaired amylase synthesis and not simply because of loss of pancreatic tissue.